Effects of Basel II on Turkish banking system - Demir, Sebahattin (My University, 2005)
Basel II (The New Capital Accord) has brought a new focus to the practice and quality of the credit ratings process and a new risk called operational risk. These new developments brought new debates and discussions in the banking sector. From the introduction date of the new accord (1999) to the accepting date (2004) academicians, the country central banks and supervisory agencies in the banking sector did lots of studies. This study is devoted to the understanding of the new capital accord, its application ways to the emerging markets, affects to the Turkish banking sector. In order to determine the readiness of internal rating systems for Basel II, a test is done on Finansbank A.Ş. which is one of the Turkish leading banks. This test has great importance because the internal rating systems of all banks will play a major role in Basel II. The findings of the study suggest that the internal rating system of Finansbank A.Ş. operates effectively and other banks can simply test their rating systems in the same way.

Basel II (Yeni Sermaye Yeterliliği) kredi derecelendirme süreci uygulama ve kalitesine yeni bir bakış açısı ve operasyonel risk olarak adlandırılan yeni bir risk anlayışı getirmiştir. Bu yeni gelişmeler bankacılık sektöründe bir çok tartışmayı da beraberinde getirmiştir. Yeni Sermaye yeterliliğinin ilk açıklanışından (1999) kabul ediliş tarihine kadar (2004) akademisyenler, ülkelerin merkez bankaları ve bankacılık denetleme kuruluşları tarafından birçok çalışma yapılmıştır. Bu çalışma ile yeni sermaye yeterliliği hakkında bilgi verilmiş, gelişmekte olan ülkelerde uygulama yöntemleri açıklanmış ve Türk bankacılık sektörüne etkileri araştırılmıştır. Ayrıca iç derecelendirme sistemlerinin Basel II karşısında hazır olup olmadıklarının tespitine yönelik lider Türk bankalarından Finansbank A.Ş. üzerinde bir test yapılmıştır. Bu testin önemi büyüktür çünkü Basel II'de bütün bankaların iç derecelendirme sistemleri büyük rol oynayacaktır. Çalışma sonucunda elde edilen bulgular Finansbank A.Ş.'nin iç derecelendirme sisteminin etkin olduğunu ve diğer bankalarında aynı yöntem ile kendi sistemlerini çok kolay ölçebileceklerini önermektedir.
Keywords: Bankalar ve Bankacılık_Türkiye; BASEL II; Muhasebe; Yönetim ve yardımcı hizmetler